Period-Doubling and Quadrupling Bifurcation of Vector Soliton Bunches in a Graphene Mode Locked Fiber Laser - Yufeng Song; Zhiming Liang; Han Zhang; Qian Zhang; Luming Zhao; Deyuan Shen; Dingyuan Tang (IEEE Photonics Journal, 2017)
Period-doubling bifurcation and period-quadrupling bifurcation of vector soliton pulses in a graphene mode locked fiber laser is experimentally observed and investigated. Not only single vector soliton but also vector soliton bunches as a unity are found to exhibit period-doubling and period-quadrupling bifurcation. The experimental results suggest that period-doubling and quadrupling bifurcation are intrinsic features of the pulses circulating in a nonlinear ring cavity, which are independent of the properties of the mode-locker in the fiber lasers.